A STUDY OF BACKGROUND RADIOACTIVITY LEVEL FOR TEKIRDAG, TURKEY - Kam, Erol; Yarar, Yascmin; Bozkurt, Ahmet (OXFORD UNIV PRESS, 2010)
The level of background radiation for Tekirdag province of north-western Turkey was assessed in this study. Radon concentrations in indoor air were determined using CR-39 nuclear track detectors. and the average Rn-222 activity was found to be 86 Bq m(-3) (equivalent to an annual effective dose of 2.2 mSv). Measurements of gamma doses in air were performed using plastic scintillators and the average absorbed gamma dose rates for indoor and outdoor were found to be 5.7 and 5 mu R h(-1), respectively, corresponding to an annual effective dose of 300 mu Sv. The radionuclide activity concentrations in soil samples collected from the study area were measured through gamma-ray spectrometry and the average activities were determined as 29, 39 and 580 Bq kg(-1) for the natural radionuclides U-238, Th-232 and K-40, respectively, and 5.2 Bq kg(-1) for the fission product Cs-137. The natural radioactivity sources resulted in an annual effective dose of 75 mu Sv. The radioactivity levels of drinking water samples were measured as 0.044 and 0.1 Bq l(-1) for gross alpha and gross beta activities using a low-background counting technique (equivalent to an annual effective dose of 9 mu Sv). The results of this study showed that the region's background radioactivity level is in agreement with most Turkish cities.
Keywords: ENVIRONMENTAL-RADIOACTIVITY; DOSE-RATES; REGION; ISTANBUL; WATERS; Environmental Sciences & Ecology; Public, Environmental & Occupational Health; Nuclear Science & Technology; Radiology, Nuclear Medicine & Medical Imaging